Prevalence and genetic diversity of clinical Vibrio parahaemolyticus isolates from China, revealed by multilocus sequence typing scheme - Han, Dongsheng; Tang, Hui; Ren, Chuanli; Wang, Guangzhou; Zhou, Lin; Han, Chongxu (Frontiers in Microbiology, 2015)
The population structure of clinical Vibrio parahaemolyticus isolates spreading in China remains undefined. We brought 218 clinical isolates from the pubMLST database originating from different regions of China collected since the year of 1990, analyzed by multilocus sequence typing (MLST), to elucidate the prevalence and genetic diversity of V. parahaemolyticus circulating in Chinese population. The MLST scheme produced 137 sequence types (STs). These STs were clustered into six clonal complexs, six doublets and 91 singletons, exhibiting a high level of genetic diversity. However, less diversity was displayed on the peptide level: only 46 different peptide sequence type (pSTs) were generated, with pST2 (44.0%, 96/218) and pST1 (15.1%, 33/218) the predominant. Further analysis confirmed all the pSTs belong to a single complex founded by pST1, pST2, pST3 and pST4. recA presented the highest degree of nucleotide diversity (0.026) and the largest number of variable sites (176) on the nucleotide level. pyrC was the most diverse locus on the peptide level, possessing the highest percentage of variable sites (9.2%, 15/163). Significant linkage disequilibrium with the alleles was detected when the Standardized Index of Association (ISA) was calculated both for the entire isolates collection (0.7169, P<0.01) and for the 137 STs (ISA =0.2648, P<0.01). In conclusion, we provide an overview of prevalence and genetic diversity of clinical V. parahaemolyticus spreading in Chinese population using MLST analysis. The results would offer genetic evidences for uncovering the microevolution relationship of V. parahaemolyticus populations.